Evaluating The Readability of Jawi To Latin Transliteration Via AI-Based Text Photography Applications - Najihatul Faridy; Allif Syahputra Bania; Bachtiar Akob (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Jawi script has lost its edge as a unifying language in the archipelago and is included as a means of communication that is starting to fade. So it is necessary to make efforts to embed digitalisation of Jawi script in order to maintain Indonesian culture in learning materials that can be accessed by the wider community using the help of the internet. In this era of artificial intelligence, there are translation machines that utilise text photography that can translate between languages, so this research focuses on efforts to preserve the Jawi script through aspects of readability for the younger generation. The research was qualitative by implementing trial and error test methods and distributing questionnaires, with the results that the use of effective applications is still limited to translation between languages ​​with the same script, but the application requires updates and upgrades to be able to translate between scripts.